STRAIN ANALYSES OF REPAIRED PIPELINES BY ENWINDING COMPOSITE MATERIALS - YANG JiCheng; WANG YanYu (Jixie qiangdu)
Rehabilitation technique of pipelines plays a very important role in ensuring the safe operation of oil and gas pipelines. Based on the internal pressure test of repaired pipelines by enwinding glass fiber composites,the finite element model of the repaired pipe is established by considering the anisotropy of the composite material. The finite element calculation results are in good agreement with the experimental results,and the accuracy of the finite element model is verified. The results show that the circumferential strain of the defect center presents a nonlinear three stage trend with the change of internal pressure after repaired. The second aggravation of circumferential strain growth trend in defect center is the characteristic of pipeline failure,this moment,the expansion of the tube wall is no longer uniform,and the elastic retention zone on both sides of the defect will cause the dent in the defect area. The research results provide reference for the design of pipeline enwinding layer.